Trzy grosze archeologa w kwestii interpretacji toponimu Alemure z Dagome iudex - Jaworski, Krzysztof (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
Among the toponyms found in Dagome iudex, the name Alemure is the most controversial. In the description of the southern border of the Gniezno state, it is located between the Oder (flumen Oddere) and Milsko (Milze). In Polish historiography, the prevailing view is that Alemure is a heavily altered version of Olomouc (J. Ptaśnik 1911) that appeared when the original document was copied. In German historiography, however, a connection between the name Alemure and the hydronym Mohra/Mura, i.e. the name of the Morawica River, a left-bank tributary of the second order of the Oder, has long been recognised (L. Giesebrecht 1843). A comparison of historical and archaeological sources indicates that it was precisely from the name Morawica, also known in the past as Morawa, that the name Alemure could have been derived through several minor transformations. The original document probably contained the entry alia mura (second/other Morawa), and when the register was compiled, the name was recorded as alemure. The area between the Morawica and Opava rivers has the highest concentration of early medieval archaeological sites in the so-called Czech Silesia, including two important strongholds located on the Morawica itself, namely Hradec nad Moravicí and Opava-Kylešovice.